HUBUNGAN ANTARA KONSEP DIRI DENGAN PERILAKU PROKRASTINASI AKADEMIK SISWA - Apriani, Pera (Tawazun: Jurnal Pendidikan Islam, 2018)
This journal explained about The Relation Between Self Concept and Students’ Academic Procratination Behaviour at SMAN 4 Kota Bogor. The aim of this research is to know there positive relationship between them at SMAN 4 Kota Bogor. This research used quantitative method, the samples was taken by sampling randomly technic with 190 respondences. The data was collected by questionaire, and analyzed by product moment pearson. The count result is 0,360. The index corelation number is not negative sign between 0,20-0.40. It can be concluded that between self concept and students’ academic procratination behaviour is low effecct. It means that there is positive Relationship Betwen Self Concept and Students’ Academic Prokratination Behaviour at SMAN 4 Bogor.